Gender specifics in entrepreneurs' personal characteristics - Karin Sirec; Dijana Mocnik (Journal for East European Management Studies, 2012)
This paper explored Slovenian entrepreneurs' personal characteristics to understand the existing gender gap in transitional countries, testing the proposed model among small and medium-sized company owners (N = 201; 32.3% female, 67.7% male). The research operationalized entrepreneurs' characteristics according to psychological and non-psychological motivation factors; the former resulted in four types of Slovenian entrepreneurs while the latter was divided into human and social capital. Significant differences emerged among genders related to certain psychological motivation factors and social capital categories, but not human capital. Women remain an unexploited source of entrepreneurship; thus, Slovenia should establish effective mechanisms to promote female entrepreneurship. – – Der vorliegende Artikel untersucht die persönlichen Merkmale slowenischer Unternehmer/innen, um die vorhandene Geschlechterschere in Transformationsländern zu verstehen. Das vorgestellte Modell wurde anhand von Unternehmenseigentümer/innen kleiner und mittelständischer Unternehmen getestet (N = 201; 32,3% weiblich, 67,7% männlich). Die Untersuchung operationalisierte Merkmale der Unternehmer/innen hinsichtlich psychologischer und nicht-psychologischer Motivationsfaktoren; erstere hatten vier slowenische Unternehmertypen zum Ergebnis, während letztere untergliedert wurden in Human- und Sozialkapital. Signifikante Unterschiede traten zwischen den Geschlechtern bezüglich bestimmter psychologischer Motivations- und Sozialkapitalfaktoren auf, nicht jedoch beim Humankapital. Frauen bleiben weiterhin eine ungenutzte Quelle des Unternehmertums; deshalb sollte Slowenien effektive Mechanismen zur Förderung weiblichen Unternehmertums etablieren.
Keywords: 650; entrepreneurship; entrepreneurship theory; SME; entrepreneurs'personal characteristics; male and female entrepreneurs